Rancang Bangun Sistem Informasi Manajemen Transaksi Penjualan Berbasis Desktop Pada CV. Permata Subang - Dwinda Putri Nuria; Dea Syah Kania; Dina Marwah Alfirahmi; Dina Amelia Alzahra; Dina Rosalina; Dadang Yusup (Peneliti.net, 2023)
Management Information System (MIS) is an integrated system that can assist organizations in conducting data management in order to produce the required information. At CV. Permata Subang, the transaction recording process is currently still done manually, which took a long time to recapitulate and search data. Therefore, the aim of this study was to design and develop a desktop-based sales transaction management information system at CV. Permata Subang. In developing this system, the Software Development Life Cycle (SDLC) will be implemented using the Waterfall model. Implementation of this system is expected to increase efficiency in managerial processes and recapitulate order data on CV. Permata Subang.